Shear Strength of Flat Joint considering Influencing Area of Bolts - Hang Lin; Penghui Sun; Yifan Chen (Advances in Civil Engineering)
Bolt is popular in the reinforcement of geotechnical engineering, which can significantly improve the strength and stability of jointed rock mass. For bolted joint, the bolting area is a certain scope instead of the entire joint surface; therefore, it is necessary to study the effect of bolt influencing area on the shear strength of rock joints. In this paper, a series of laboratory direct shear tests were executed on the bolted joints to explore the influence of bolts on the joint shear strength, as well as the influencing area of bolt. Via successively changing bolting angle and bolt number, the shear stress-shear displacement curves of bolted joints were recorded and the variation law of shear strength was analyzed. Based on the assumption of the circular influencing area of bolt, the influence coefficient m (defined as the diameter ratio of the influencing area to the bolt) was introduced to establish the theoretical calculation model of the shear strength of bolted joint, which was verified by test results. Furthermore, the value of m was changed, and the shear strengths of bolted joints under different bolting condition were calculated to compare with the test results. The average relative error Eave was selected to determine the optimal value of m under the corresponding bolting condition, and it tends to sufficiently small values under the case of m > 30 for one-bolted joint and m > 25 for two-bolted joint, as well as m > 20 for three-bolted joint, which demonstrates that m can be applied to effectively calculate the actual influencing area of bolt.